Being-towards-grief: rethinking death awareness. (3rd July 2021) - Sköld, Alfred Bordado
ABSTRACT: In this article I develop the notion of Being-towards-grief as a way of conceptualising the blurred intersection between relationality and finitude. In contrast to an existential philosophical and psychological tradition that has privileged one's own death in a rationalised fashion, I argue that we become aware of death through the relentless possibility of the other dying and the uncertainty and distress that this implies. Furthermore, I suggest that this encounter is paramount to an inherently ethical process of subjectification. I become who I am through an encounter with the possibility of the death of the other and the responsibility that this implies. Instead of a resolute and future-oriented life affirmation, the death awareness that Being-towards-grief entails, points to an acceptance of and humbleness with regard to human limitations, and gratitude for a common past.